Transcultural Aspects of Men Embodiment. The Body Self Analysis of Polish and Danish Men Who Do Martial Arts - Mirucka, Beata (INSTED: Interdisciplinary Studies in Education & Society, 2014)
The study investigated the problem of relation between the body self and the cultural context. The body self is understood as one of the central personality aspect containing three interdependent dimensions. The first two are: functions of the body self (sensetioning, interpretation, and regulation) and psychic representations of the body self. The subjective (functions) and objective (representations) aspects of body self determine the sense of somatic identity. The psychic representations of the body built the structure of body self. The aim of the article is to explore the structure of the body self in the groups of men ? Polish and Danish that train the martial arts (66 men at age 17?27 years). All of them were examined by the Questionnaire of Body Self by B. Mirucka. Conclusions from the study were that there is a significant relation between the structure of the body self (the representation of body schema, the representation of bodily needs and the representation of knowledge) and the cultural context ? Polish and Danish.